Becoming aware of subliminal responses: An EEG/EMG study on partial error detection and correction in humans. (November 2019) - Ficarella, Stefania C.; Rochet, Nicolas; Burle, Boris
Abstract: In experimental settings, most overt behavioral errors are consciously perceived. They are, however, only the tip of the iceberg, and electromyographic recording of the muscles involved in the response reveals subthreshold incorrect response activations. Although they are all efficiently corrected, such "partial errors" are poorly consciously detected. Electroencephalographic recordings (CSD estimate), revealed the sequence of cortical activities that lead, or not, to conscious detection. Besides medio-prefrontal activities related to action monitoring and error detection, the motor command sent by the primary motor cortices also differed between detected and undetected partial errors: while it develops identically, it is stopped earlier for the latter than for the former, suggesting a critical role in partial error detection. Second, the analysis of the "Error positivity" – Pe, classically linked to error awareness, confirmed its absence just after partial errors, be they detected or not. However, a Pe occurs after the corrective response of partial errors that were detected, suggesting that we become aware of our partial errors only after their correction. The implication of these results for the link between consciousness and cognitive control are discussed.